Kritik terhadap Teologi Proses dan Pembelaan terhadap Pandangan “Greater Good” dalam Menanggapi Masalah Kejahatan - Jessica Novia Layantara (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2017)
Kata-kata kunci: Teodisi, Soft-determinism, Kompatibilisme, Kedaulatan Allah, Masalah Kejahatan, Holocaust, Auschwitz, Teologi Proses, Pembelaan Kehendak Bebas, Teodisi Pembentukan Jiwa, Greater Good Theodicy, John Calvin, John Feinberg English: Throughout the ages Christian theologians have attempted to understand, from a philosophical vantagepoint, the problem of evil. The Church Fathers as well as theologians during the era of the Reformation have offered a solution that argues from the basis of the greater good. However, solutions of that nature seem to ring hollow when one considers the magnitude and scope of the Holocaust (Auschwitz). In light of that historical reality traditional solutions to the problem of evil seem inadequate. Process theology attempts to overcome the impasse by restricting the attributes of God. The purpose of this article is to critically evaluate contemporary solutions to the problem of evil, especially process theology, as inadequate solutions. Further, to argue for the traditional positional argument of the greater good as offering a tenable solution. Keywords: Theodicy, Soft-determinism, Compatibilism, Sovereignty of God, Problem of Evil, Holocaust, Auschwitz, Process Theology, Free Will Defense, Soul-shaping Theodicy, Greater Good Theodicy, John Calvin, John Feinberg